Prediction of heat transfer coefficients and friction factors for evaporation of R-134a flowing inside corrugated tubes - Laohalertdecha, S.; Aroonrat, K.; Dalkilic, A. S.; Mahian, O.; Kaewnai, S.; Wongwises, S. (SPRINGER, 2014)
In this study, experimental and simulation studies of the evaporation heat transfer coefficient and pressure drop of R-134a flowing through corrugated tubes are conducted. The test section is a horizontal counter-flow concentric tube-in-tube heat exchanger 2.0 m in length. A smooth tube and corrugated tubes with inner diameters of 8.7 mm are used as the inner tube. The outer tube is made from a smooth copper tube with an inner diameter of 21.2 mm. The corrugation pitches used in this study are 5.08, 6.35, and 8.46 mm. Similarly, the corrugation depths are 1, 1.25, and 1.5 mm, respectively. The results show that the maximum heat transfer coefficient and pressure drop obtained from the corrugated tube are up to 22 and 19 % higher than those obtained from the smooth tube, respectively. In addition, the average difference of the heat transfer coefficient and pressure drop between the simulation model and experimental data are about 10 and 15 %, respectively.
Keywords: TWISTED TAPE INSERTS; TURBULENT-FLOW; PRESSURE-DROP; CONDENSATION; ENHANCEMENT; COMBINATION; ANNULUS; COIL; Thermodynamics; Mechanics